A Currency Union for the Caribbean - Worrell, Rupert (IMF Working Papers; Working Paper ;, 2003)
The experiences of Caribbean Economic Community countries show that exchange rate depreciation in these countries is inflationary, and that, while changes in the relative prices of tradables may affect exports, tourism, and imports, nominal exchange rate changes have no predictable effect on those relative prices. Under these circumstances, economic literature indicates that a fixed exchange rate regime is optimal, and Caribbean countries with (quasi-) currency boards have been successful in maintaining durable exchange rate pegs. Commitment to a currency board is a potentially vital step in achieving a currency union for the Caribbean.